The solder joint characterization in green WLCSP - Lee, J.C.B.; Jun-Yuan Chen; Pel Chun Chen; Li, S.W. (2004 54th Electronic Components and Technology Conference, 2004)
WLCSP with Ni/Cu UBM and SnAgCu solder interconnect comply completely with European ROHS regulation. SnAgCu solder presents best solder joint thermal fatigue life in laminate BGA type package to organic PCB during gentle TCT condition, but whether means it can also work in silicone die level package to organic PCB due to larger CTE mismatch during temperature cycling, the further study and more confident data is still necessary to be explored. In this report, the interfacial metallurgical reactions of solder joint of the combination of 0.3mm SnAgCu and Sn0.7Cu solder ball and different melting point solder pastes such as Sn37Pb, Sn7ZnAl and Sn3.0Ag0.5Cu will be investigated in the wafer level CSP package with 0.5mm ball pitch. After appropriate SMT process at low, medium and high reflow temperature respectively on NSMD FR4 PCB with Cu-OSP surface finish, the sample is subject to TCT (-40/spl sim/125/spl deg/C) 1000 cycle, then are followed by mechanical package shear test with larger strain rate. The diverse failure mode is recorded to illustrate the solder joint mechanism. The cross-section of the solder joint is also scrutinized by SEM/EDX to observe metallurgical evolution in the interface and solder bulk itself over the thermal cycle. The relationship among the fracture morphology, package shear strength, and solder paste type will be discussed in the study. A mature wafer level CSP with Sn37Pb solder ball will be used for comparison as well.